LEARNING INTERACTION OF TEACHER AND STUDENT (ON THE MATERIAL OF GERMAN LANGUAGE) - Amelina, S.M. (Pedagogy of Higher and Secondary Education, 2009)
Educational interaction between teachers and students ( based on material in German ). Various forms of educational interaction between the teacher and the student at German lesson are analized. The effectiveness of communicative structure in partners’ work is demonstrated. Wider use of projects, business and role plays , "Fall-Studien" method is suggested.